Controlling Pyrene Association in DNA Duplexes by B‐ to Z‐DNA Transitions. (25th September 2019) - Nakamura, Mitsunobu; Takada, Tadao; Yamana, Kazushige
Abstract: B‐ to Z‐DNA transitions play a crucial role in biological systems and have attracted the interest of researchers for their applications in DNA nanotechnology. DNA and DNA analogues have also been used as templates to construct helical chromophore associations with π interactions. In this work, the B‐ to Z‐DNA transition‐induced switching of pyrene in an association manner was evaluated using DNA duplexes with non‐nucleosidic pyrene residues in the middle of d(CG) repeat sequences. One of the pyrene‐labeled DNAs was shown to exhibit inverted exciton coupled circular dichroism signals upon pyrene association through a B‐ to Z‐DNA transition. This observation indicates that pyrene association switches the DNA conformation from right‐ to left‐handed. Interestingly, the fluorescence of the pyrene‐labeled DNA duplex also dynamically changed upon switching of the pyrene in an association‐based manner. Taken together, these studies demonstrate that pyrene‐labeled DNA shows promise as a chiroptical molecular switch. Abstract : DNA switch : Pyrene‐labeled DNA duplexes exhibited inverted exciton coupled circular dichroism signals upon pyrene association through a B‐ to Z‐DNA transition (see figure). This observation indicates that the pyrene association switched the conformation of the structure from right‐ to left‐handed. Thus, pyrene‐labeled DNA has the potential to serve as a chiroptical molecular switch.